On categories with semidirect products - Martins-Ferreira, Nelson (2010)
We characterize pointed categories having semidirect products in the sense of D. Bourn and G. Janelidze ([3]) providing necessary and sufficient conditions for a pointed category to admit semidirect products and interpreting these conditions in terms of protomodularity and exactness of certain split chains.